Digital technologies and power dynamics in the organization: A conceptual review of remote working and wearable technologies at work. Issue 6 (13th April 2020) - Miele, Francesco; Tirabeni, Lia
Abstract: In this article, we examine the kinds of control practices that emerge with the introduction of digital technologies, and how these technologies are employed to shape power within workplaces. We present a comparative conceptual review of work practices by contrasting remote work and the use of workplace wearables. We trace forms of power and control that have been enacted with the adoption of these work‐related technologies and associated practices. We find that the prevailing literature focuses on the practices enacted by management in order to control workers and exert power over them, and we propose that a more comprehensive approach be taken. In support of this view, we show how the concept of appropriation emerges from science and technology studies, and we argue that such a concept would be useful for exploring how workers use and incorporate digital technologies into their daily lives, thus reshaping power in organizations.